An overview of the immune response and Arginase I on CHIKV immunopathogenesis. (October 2019) - Lombardi Pereira, Ana Paula; Suzukawa, Helena Tiemi; do Nascimento, Aline Miquelin; Bufalo Kawassaki, Aedra Carla; Basso, Camila Regina; dos Santos, Dayane Priscila; Damasco, Kamila Falchetti; Machado, Laís Fernanda; Amarante, Marla Karine; Ehara Watanabe, Maria Angelica
Abstract: Chikungunya virus (CHIKV) is mosquito-borne alphavirus that has caused epidemics around the world. Many individuals affected by the disease may experience joint pain that persists for months after the acute phase. The pathophysiology of viral arthritis is not completely elucidated. And it is important to emphasize that the effects of the viral infection in each host may depend on host factors that include immune response, as well as factors specific to the virus as tissue tropism. The main pathway for the response against viral infection is through induction of type I interferon (IFN-I), whose function is important to control viral replication. Beside this, T cell and macrophage mediated immunopathology in CHIKV infections has been reported. It has been demonstrated that some association with the Arginase I and macrophages type II are involved in the infection profile along with myeloid-derived suppressor cells (MDSC) that are responsible for T cell suppression. Therefore, in this review, will be discuss an overview on CHIKV immunopathogenesis and the importance of Arginase I.